Insulin adherence and the associated factors among patients with type 2 diabetes mellitus at the Hospital Queen Elizabeth II, Sabah - Yong, Siew Yee; Goh, Greta Miranda; Loh, Huai Heng (Springer Nature, 2020)
Aim The purposes of this study were to: (a) determine the insulin adherence rate and reasons for non-adherence among patients with T2DM, (b) determine the relationship between the Health Belief Model (HBM) construct and insulin adherence, (c) assess the patient’s characteristics that influence the Health Belief Model (HBM) construct, and (d) identify the predictors of insulin non-adherence among patients with T2DM.